Experiment with text summarization as a positive hierarchical fuzzy logic ranking indicator for domain specific retrieval of Malay translated hadith - Bin Rodzman S.B.; Kamal Ismail N.; Rahman N.A.; Ahmad Aljunid S.; Rahman H.A.; Nor Z.M.; Muhammad Naim Ku Khalif K.; Yunus Mohd Noor A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus